High‐Visible‐Light Photocatalytic Activity of ZnO–Au Nanocomposites Synthesized by a Controlled Hydrothermal Method. Issue 16 (1st July 2021) - Yao, Chujun; Lin, Jiamin; Wu, Li; Li, Lequn; Xu, Ning; Sun, Jian; Wu, Jiada
Abstract : Powdered Au‐nanoparticle‐modified ZnO (ZnO–Au) nanocomposites having high photocatalytic activity are synthesized via a simple, facile, and controlled method. Through hydrothermal reactions, ZnO nanorods are first grown and the rod surface is then decorated with Au nanoparticles, with the number of Au nanoparticles being adjustable by changing the concentration of tetrachloroauric acid (HAuCl4 ) in the precursor hydrothermal solution. The ZnO nanorods have an average length of 2 μm and diameter of 300 nm, and the Au nanoparticles are nearly spherical sized between 5 and 10 nm. The ZnO–Au nanocomposites have a higher light absorption capacity and lower carrier recombination rate than the bare ZnO nanorods, which is attributed to the plasmonic sensitizing of Au nanoparticles and makes the synthesized ZnO–Au nanocomposites photocatalytically active. The photocatalytic activity of the ZnO–Au nanocomposites is investigated by degrading rhodamine B (RhB) under visible light illumination, demonstrating that RhB can be photocatalytically degraded more efficiently with the ZnO–Au nanocomposites than with the bare ZnO nanorods, with the rate constant increasing from 6.36 × 10 −4 min −1 for the bare ZnO nanorods to 1.19 × 10 −2 min −1 for the ZnO–Au nanocomposites. The ZnO–Au nanocomposites also exhibit good photocatalytic stability and can be reused as photocatalysts. Abstract : The surface of powdered ZnO nanorods is decorated with Au nanoparticles via a controlled hydrothermal method based on hydrothermal reactions, forming ZnO–Au nanocomposites in the form of Au‐decorated ZnO nanorod powders. The prepared ZnO–Au nanorod powders have much higher photochemical activity than bare ZnO nanorods and can be used as photocatalysts to efficiently photodegrade organic pollutants.